Enhancing the Mechanical Properties of Ultra-High-Performance Concrete (UHPC) Through Silica Sand Replacement with Steel Slag - Hadi Bahmani; Hasan Mostafaei; Paulo Santos; Niyousha Fallah Chamasemani (Buildings, 2024)
In modern construction, increasing the sustainability of materials without sacrificing performance is crucial. Ultra-High-Performance Concrete (UHPC) is known for its exceptional strength and durability. However, incorporating waste and optimizing the mix is still a key focus. The main goal of this article is to evaluate the enhancement of the mechanical properties of UHPC by replacing silica sand with steel slag at various percentages (25%, 50%, 75%, and 100%). With this purpose, we measured the compressive, tensile, and flexural strengths, as well as relative density and water absorption. It was found that the best mechanical performance of UHPC occurs at 50% replacement, exhibiting a maximum compressive strength of 126 MPa (+13.5%), a bending strength of 11.6 MPa (+20.8%), and a tensile strength of 7.2 MPa (+6.5%). Moreover, for the same steel slag replacement, 5.1% decrease in the CO2 eq. emissions was found. However, exceeding the 50% threshold led to a deterioration of UHPC’s mechanical properties, and the SEM images revealed that this was mainly caused by the weakened bond between the cement matrix and the aggregates. Thus, it was concluded that the use of steel slag may significantly improve the structural integrity of UHPC when the adequate replacement percentage is adopted (around 50%), being a viable alternative to traditional aggregates that also has environmental advantages (e.g., reduced carbon emissions).